Ratio Decidendi Putusan Mahkamah Agung Nomor 2290K/PDT/2012 Tentang Pinjam Meminjam Uang Dengan Surat Pengakuan Utang dan Kuasa Menjual - Syauqi, Ahmad; Bakri, Muhammad; Permadi, Iwan (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
Tthis study aimed to analyze the validity of debt recognition letters and selling authorities (evidence P-2 and evidence P-3), the basis for judges’ considerations, and the legal consequences of the Supreme Court Decision Number 2290 K/Pdt/ 2012 for debtors and creditors. The method used in this study was normative juridical research with a statutory approach and a case approach. The results of the systematic interpretive analysis showed that the debt recognition letter (evidence P-2) and selling authorities (evidence P-3) in the Supreme Court Decision Number 2290 K/Pdt/ 2012 could be declared invalid. Juridically, the judges’ considerations were considered insufficient in examining the truth of the events in the Supreme Court Decision Number 2290 K/Pdt/2012. The legal consequences that occurred after the verdict, the creditor could have collateral for the land-based on an invalid debt acknowledgment but legalized by the panel of judges in the decision. The legal consequence for the debtor, the legal action to defend the land that was carried out by him was considered an act against the law